Innovative Methods and Models of Collaboration in the Field of Pedagogical Prevention of Xenophobia, Anti-Semitism and Right-wing Extremism: Chances and Perspectives for a Better Cooperation between Formal and Non-formal Education in Germany - Johansson, Susanne (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryXenophobic, anti-Semitic and right-wing extremist attitudes continue to pose a serious problem and an ongoing challenge among German youth. Since problematic attitudes and risk groups change with time and according to political circumstances and social change, there is a constant need for the development of new practices and the innovative adaption of existing strategies of pedagogical prevention. Evaluations of German government model programs aimed at the pedagogical prevention of xenophobia, anti-Semitism and right-wing extremism show that sustainable prevention effects can be reached on the basis of productive cooperation between formal and non-formal educators. In order to improve their efforts toward prevention and cooperation, both partners have to refine their collaborative models and their methodology as well as to react better to changes in the composition of groups of participants and students in a society characterized by immigration and globalization.Key words: right-wing extremism, xenophobia, evaluation, prevention, non-formal education.